The language of websites - Boardman, Mark (Routledge, 2005)
The Intertext series has been specifically designed to meet the needs of contemporary English Language Studies.Working with Texts:a core introduction to language analysis (second edition 2001) is the foundation text, which is complemented by a range of 'satellite' titles. These provide students with hands-on practical experience of textual analysis through special topics, and can be used individually or in conjunction with Working with Texts. The Language of Websites: *explores the ways in which websites use and present language *covers many different types of web-based interaction, from buying online and auction sites, to search engines, email links and chatrooms *considers the structures of language online, such as audience interaction and how hypertext alters narrative structure * features a full glossary.